How is Student Entrepreneurial Motivation at Ahmad Dahlan University? - Sugiharto, Gatot; Bhakti, Caraka Putra; Fajri, Choirul; Anwar, Astrid Nabilah; Ariyani, Dian (International Journal of Educational Management and Innovation, 2024)
This study aims to describe the entrepreneurial motivation of students who have taken entrepreneurship courses. The technique used in this research is purposive sampling and accidental sampling. This research was conducted at Ahmad Dahlan University, with several respondents of 801 students. The instrument used is an entrepreneurial motivation scale adapted by Nugroho (2017) using the motivational aspects developed by Vanesaar et al. (2006), namely the aspects of ambition for freedom, self-Realisation, and pushing factors. Test this validity by comparing the r count's value with the r table, then by calculating the r count (rxy) for each item using the CORREL formula in excel. Reliability is calculated using the Cronbach alpha formula. It is found that student entrepreneurship motivation is in the high category. The highest aspect is in the Ambition for Freedom aspect, and the lowest is in Self Realisation. The Ambition for Freedom aspect with details strongly agrees with a frequency of 218 (27.22%), and the agree category with a frequency of 518 (64.67%). Aspects of Self Realisation with respondents' answers in the strongly agree category with a frequency of 153 (19.10%), the agree category with a frequency of 357 (44.57%), the category disagrees with a frequency of 291 (36.33%).